In vitro evaluation of the response of human tendon‐derived stromal cells to a novel electrospun suture for tendon repair. Issue 3 (15th March 2021) - Nezhentsev, Andrey; Abhari, Roxanna E.; Baldwin, Mathew J.; Mimpen, Jolet Y.; Augustyniak, Edyta; Isaacs, Mark; Mouthuy, Pierre‐Alexis; Carr, Andrew J.; Snelling, Sarah J. B.
Abstract : Recurrent tears after surgical tendon repair remain common. Repair failures can be partly attributed to the use of sutures not designed for the tendon cellular niche nor designed for the promotion of repair processes. Synthetic electrospun materials can mechanically support the tendon while providing topographical cues that regulate cell behavior. Here, a novel electrospun suture made from twisted polydioxanone (PDO) polymer filaments is compared to PDS II, a clinically used PDO suture currently utilized in tendon repair. We evaluated the ability of these sutures to support the attachment and proliferation of human tendon‐derived stromal cells using PrestoBlue and scanning electron microscopy. Suture surface chemistry was analyzed using x‐ray photoelectron spectroscopy. Bulk RNA‐Seq interrogated the transcriptional response of primary tendon‐derived stromal cells to sutures after 14 days. Electrospun suture showed increased initial cell attachment and a stronger transcriptional response compared with PDS II, with relative enrichment of pathways including mTorc1 signaling and depletion of epithelial‐to‐mesenchymal transition. Neither suture induced transcriptional upregulation of inflammatory pathways compared to baseline. Twisted electrospun sutures therefore show promise in improving outcomes in surgical tendon repair by allowing increased cell attachment while maintaining an appropriate tissue response.